MICROSERVICES WITH GO building scalable and reliable Go microservices - Shuiskov, Alexander (PACKT PUBLISHING LIMITED, 2022)
Build, scale, and maintain microservices in Golang with ease. Key Features Create and organize well-structured Go microservices Learn industry best practices and gain insights into Go microservice development tools, patterns, and solutions Cover hands-on Golang examples in each chapter Book Description This book covers the key benefits and common issues of microservices, helping you understand the problems microservice architecture helps to solve, the issues it usually introduces, and the ways to tackle them. You'll start by learning about the importance of using the right principles and standards in order to achieve the key benefits of microservice architecture. The following chapters will explain why the Go programming language is one of the most popular languages for microservice development and lay down the foundations for the next chapters of the book. You'll explore the foundational aspects of Go microservice development including service scaffolding, service discovery, data serialization, synchronous and asynchronous communication, deployment, and testing. After covering the development aspects, you'll progress to maintenance and reliability topics. The last part focuses on more advanced topics of Go microservice development including system reliability, observability, maintainability, and scalability. In this part, you'll dive into the best practices and examples which illustrate how to apply the key ideas to existing applications, using the services scaffolded in the previous part as examples. By the end of this book, you'll have gained hands-on experience with everything you need to develop scalable, reliable and performant microservices using Go. What you will learn Get familiar with the industry's best practices and solutions in microservice development Understand service discovery in the microservices environment Explore reliability and observability principles Discover best practices for asynchronous communication Focus on how to write high-quality unit and integration tests in Go applications Understand how to profile Go microservices Who this book is for This book is for all types of developers, from people interested in learning how to write microservices in Go to seasoned professionals who want to take the next step in mastering the art of writing scalable and reliable microservice-based systems. A basic understanding of Go will come in handy.